2005
DOI: 10.1016/j.jcrysgro.2004.11.237
|View full text |Cite
|
Sign up to set email alerts
|

Melting of a DPPC lipid bilayer observed with atomic force microscopy and computer simulation

Abstract: Atomic force microscopy imaging of a supported bilayer of the phospholipid DPPC revealed the presence of thin lines, which were thought to be the boundaries of domains with a different orientation. Temperature-controlled AFM showed that the melting from the gel state L b 0 to the fluid L a phase starts on these lines. The observed onset of melting at 40.3 1C compared well to reported DSC measurements.The same mechanism of melting was observed in computer simulations on a bilayer of a coarse-grained lipid model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 11 publications
2
23
0
4
Order By: Relevance
“…The findings so far are contradictory. Melting temperature and broadness of the melting transition of SSMs are reported to either perfectly reproduce the results obtained from vesicular systems [6,8] or in contrary, display a substantial increase in T M accompanied by a large broadening of the transition of a few degrees. [7,9,11] Decoupling of the leaflets, as reported by Feng et al [5] may explain the occurrence of the broad transition of phosphocholine membranes.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…The findings so far are contradictory. Melting temperature and broadness of the melting transition of SSMs are reported to either perfectly reproduce the results obtained from vesicular systems [6,8] or in contrary, display a substantial increase in T M accompanied by a large broadening of the transition of a few degrees. [7,9,11] Decoupling of the leaflets, as reported by Feng et al [5] may explain the occurrence of the broad transition of phosphocholine membranes.…”
supporting
confidence: 51%
“…[1][2][3][4] Recently, a series of papers has been published on the measurement of the main phase transition temperature (T M ) of solid supported phospholipid bilayers by means of temperature-controlled atomic force microscopy. [5][6][7][8][9][10][11][12][13] Knowledge of T M is pivotal if lateral organization, fluidity and elasticity are of interest or need to be adjusted. The findings so far are contradictory.…”
mentioning
confidence: 99%
“…These findings might also explain the frequently observed differences in T m . 46,[51][52][53][54] In order to rule out that variation in surface quality accounts for inconsistent results on the thermotropic properties of membranes, it is inevitable to provide an internal standard, i.e., a membrane of known thermomechanical properties. This is one of the greatest benefits of individually addressable microstructured bilayers in the way we prepare them here since two stripes of different composition can be deposited adjacent to each other, which allows us to use one membrane stripe as the internal standard, while the others can be varied in composition.…”
Section: A Thermotropic Phase Transition Of Microstructured Dmpc Bilmentioning
confidence: 99%
“…However, after thermal incubation at 40 °C, the fluorescent intensity of the suspension abruptly increased from about 400 to 2000, which was owing to that liposomes bilayers melting at 41.6 °C as reported in references [33][34] . The abruptly increase also suggested that the liposomes were successfully prepared and the calcein encapsulated within the liposomes lumen.…”
Section: Fig1 Calcein Release With Temperaturementioning
confidence: 51%